Efisiensi dan Potensi Industri Manufaktur Propinsi Jawa Timur - Titik, Crisanty Sutristyaningtyas (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2018)
This study aims to determine which manufacturing sub-sectors in East Java are efficient and which manufacturing sub-sectors are the basis or superior in East Java by using the data in 2011. The analytical method used to measure efficiency level with non parametric approach by using Data Envelopment Analaysis (DEA). While to identify the sub-sector of base or superior used two tools that is Location Quetion (LQ) and Specialization Index (IS). The results showed that the industrial sub-sector in East Java has achieved the most efficiency and about the base sector almost 50% of the East Java sub-sector is the base sector that there are 11 sub- sectors, this result is also reinforced by the Specialization Index which is also in the same direction that there are 11 positive sub-sectors of the 24 existing sub- sectors.